Exercise-induced arterial hypoxemia is not different during cycling and running in triathletes - Laursen, P. B.; Rhodes, E. C.; Langill, R. H.; Taunton, J. E.; McKenzie, D. C. (Scandinavian Journal of Medicine & Science in Sports, 2005)
This study examined the effect of running and cycling on exercise-induced arterial hypoxemia (EIAH) in individuals well trained in each modality. Thirteen male triathletes (±SD: age=36±5 years, mass=69±8 kg, body fat=12±1%) performed progressive exercise to exhaustion during cycle ergometry and treadmill running. Gas exchange was determined, while oxyhemoglobin saturation (SaO2) was measured with an ear oximeter. At maximal exercise, the respiratory exchange ratio (1.15±0.06 vs. 1.10±0.05) and the ventilatory equivalent for oxygen uptake (37.6±3.8 vs. 34.2±2.7) were greater during cycling vs. running (P<0.05). However, there were no differences at maximal exercise in oxygen uptake (64.4±3.2 vs. 67.0±4.6 mL kg1 min1), SaO2 (93.4±2.8% vs. 92.6±2.2%), or the ventilatory equivalent for carbon dioxide (E/CO2; 33.1±3.1 vs. 31.0±3.1), during cycling vs. running, respectively. During submaximal exercise, the E/CO2 was less for cycling (26.0±1.0) compared with running (29.1±0.4; P<0.05), but this had no apparent effect on the SaO2 response. In conclusion, EIAH was not significantly different during cycling and running in athletes who were well trained in both exercise modalities.